2020
DOI: 10.1016/j.jcis.2020.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Directly probing surfactant adsorption on nanoscopic trenches and pillars

Abstract: HypothesisConfinement causes a change in the amount of surfactant adsorbed and adsorption morphology. ExperimentsTwo cationic surfactants, tetradecyltrimethylammonium bromide (TTAB) and cetylpyridinium chloride (CPC) were adsorbed at the silica-water interface. Atomic force microscopy (AFM) force curves were measured on 50 nm and 80 nm wide trenches. Force curves were also measured on silica pillars, and the results were quantified based on distance from the edge. FindingsTrenches: Adsorbed surfactants films i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Numerous studies have investigated surfactant mesophases formed on solid substrates, and it has been demonstrated that the surface properties of substrates, including hydrophilicity and heterogeneity, can modify the interfacial curvature of surfactant mesophases formed on them [ 18 ]. Moreover, Grady et al [ 106 ] directly probed the surfactant mesophases on nanoscopic trenches and pillars using an atomic force microscope. They found that the effect of surface physical heterogeneity on the structure of surfactant mesophases extends to lengths much longer than those of individual surfactant molecules (approximately 50 nm vs. 2 nm).…”
Section: Effect Of Substrate On Tfc’s Structures and Performancementioning
confidence: 99%
“…Numerous studies have investigated surfactant mesophases formed on solid substrates, and it has been demonstrated that the surface properties of substrates, including hydrophilicity and heterogeneity, can modify the interfacial curvature of surfactant mesophases formed on them [ 18 ]. Moreover, Grady et al [ 106 ] directly probed the surfactant mesophases on nanoscopic trenches and pillars using an atomic force microscope. They found that the effect of surface physical heterogeneity on the structure of surfactant mesophases extends to lengths much longer than those of individual surfactant molecules (approximately 50 nm vs. 2 nm).…”
Section: Effect Of Substrate On Tfc’s Structures and Performancementioning
confidence: 99%